Aerodynamic optimization of a bobsleigh configuration - Berton, E.; Favier, D.; Agnes, A.; Pous, F. (International Journal of Applied Sports Sciences, 2004)
The study focuses on the performance improvement of a bobsleigh team as a function of number of parameters including aerodynamics of the bobsleigh shape and relative position of the athletes inside the bobsleigh (optimized as a function of athletes morphological characteristics as well as different parts of their equipment, helmets shape and position). This performance optimization problem is investigated through a close collaboration with the French Olympic bobsleigh team and by means of a wind-tunnel simulation with an upstream velocity representative of the actual race bobsleigh velocity on the track slope. The aerodynamic response of the crew-sled ensemble to any modification of the attitude in the wind-tunnel flow is analyzed in terms of overall aerodynamic drag force measurements. Such an experimental approach exhibited a clear identification of several parameters depending on the attitude of the athletes and well suited to improve the performance in terms of the drag coefficient reduction and thus of the bobsleigh highest velocity increase. In addition to beneficial effects resulting from the addition of deflectors appendices installed on the external bobsleigh careenage, two major factors of the drag reduction are shown to be on one hand the optimized relative position of the upper part of the athletes bodies and on the other hand the specific position of the Brakeman (last athlete) which has for effect to reduce the wake contribution to the total drag force. Tlie study focuses on the performance improvement of a bobsleigh team as a function of number of parameters including aerodynamics of tlie bobsleigh shape and relative position of the athletes inside the bobsleigh (optimized as a function of athletes morphological diaracteristics as well as different parts of tlieir equipment, helmets shape and position). This performance optimization problem is investigated througl a close collaboration with the French Olympic bobsleigh team and by means of a wind-tunnel simulation with an upstream velocity representative of the actual race bobsleigh velocity on the track slope. The aerodynamic response of the crew-sled ensemble to any modification of the attitude in the wind-tunnel flow is analyzed in terms of overall aerodynamic drag force measurements. Such an experimental approach exhibited a clear identification of several parameters depending on the attitude of the athetes and well suited to improve the performance in terms of the drag coefficient reduction and thus of tlie bobsleigh highest velocity increase. In addition to beneficial effects resulting from the addition of deflectors appendices installed on the external bobsleigh careenage, two major factors of the drag reduction are shown to be on one hand the optimized relative position of the upper part of the atltletes bodies and on the other hand the specific position of the Brakeman (last athlete) which has for effect to reduce the wake contribution to the total drag force.